Characterisation of the semi-volatile component of Dissolved Organic Matter by Thermal Desorption – Proton Transfer Reaction – Mass Spectrometry. Issue 1 (December 2017) - Materić, Dušan; Peacock, Mike; Kent, Matthew; Cook, Sarah; Gauci, Vincent; Röckmann, Thomas; Holzinger, Rupert
Abstract Proton Transfer Reaction – Mass Spectrometry (PTR-MS) is a sensitive, soft ionisation method suitable for qualitative and quantitative analysis of volatile and semi-volatile organic vapours. PTR-MS is used for various environmental applications including monitoring of volatile organic compounds (VOCs) emitted from natural and anthropogenic sources, chemical composition measurements of aerosols, etc. Here we apply thermal desorption PTR-MS for the first time to characterise the chemical composition of dissolved organic matter (DOM). We developed a clean, low-pressure evaporation/sublimation system to remove water from samples and coupled it to a custom-made thermal desorption unit to introduce the samples to the PTR-MS. Using this system, we analysed waters from intact and degraded peat swamp forest of Kalimantan, Indonesian Borneo, and an oil palm plantation and natural forest in Sarawak, Malaysian Borneo. We detected more than 200 organic ions from these samples and principal component analysis allowed clear separation of the different sample origins based on the composition of organic compounds. The method is sensitive, reproducible, and provides a new and comparatively cheap tool for a rapid characterisation of water and soil DOM.